Market Approach in Environmental Protection and Response to Climate Change: US Experience - Hoang Nam, Nguyen; Thi Hue, Hoang; Thi Thu Nhan, Nguyen (VNU Journal of Science: Policy and Management Studies, 2018)
Abstract: Promoting market-based approach to reduce burden on the State budget and mobilize resources from various sectors of the society, especially in the field of environmental protection and response to climate change, has become a global trend. This paper analyzes the essence of this approach and discusses the conditions required for its successful implementation, based on experiences from the United States and some other developed market economies. Accordingly, the article also discusses some specific solutions that can be applied in Vietnam in implementing this approach. Keywords: Market-based approach, command and control approach, market-based solutions, environmental protection, climate change response. References [1] Hepburn, C. (2010). Environmental policy, government, and the market. Oxford Review of Economic Policy, 26(2), 117-136. [2] Stavins, R. N. (2006). Market-based environmental policies: what can we learn from US experience (and related research)? In J. Freeman & C. D. Kolstad (Eds.), Moving to markets in environmental regulation: Lessons from twenty years of experience (pp. 19-47): Oxford University Press. [3] Zhang, B. (2013). Market-based solutions: An appropriate approach to resolve environmental problems. Chinese Journal of Population Resources and Environment, 11(1), 87-91. [4] Eskeland, G. S., & Jimenez, E. (1992). Policy instruments for pollution control in developing countries. The World Bank Research Observer, 7(2), 145-169. [5] Cole, D. H., & Grossman, P. Z. (1999). When is command-and-control efficient-institutions, technology, and the comparative efficiency of alternative regulatory regimes for environmental protection. Wis. L. Rev., 887. [6] Engel, S., Pagiola, S., & Wunder, S. (2008). Designing payments for environmental services in theory and practice: An overview of the issues. Ecological economics, 65(4), 663-674. [7] Chavez, C. A., Villena, M. G., & Stranlund, J. K. (2009). The choice of policy instruments to control pollution under costly enforcement and incomplete information. Journal of Applied Economics, 12(2), 207-227. [8] Lloyd, W. F. (1833). Two Lectures on the Checks to Population. London: University of Oxford. [9] Coase, R. H. (1960). The problem of social cost. Journal of Law and Economics, 3, 1-44. [10] Wirtz, B. (2017). The Essence of Free Market Environmentalism: Protection through private property. Maastricht University Journal of Sustainability Studies, 3. [11] Butler, L. L. (1985). Allocating consumptive water rights in a riparian jurisdiction: Defining the relationship between public and private interests. U. Pitt. L. Rev., 47, 95. [12] Wiel, S. C. (1979). Water Rights in the Western States (Vol. 1): Arno Press. [13] 19 U.S.C. § 1677 (18). Retrieved from https://www.law.cornell.edu/uscode/text/19/1677 [14] Waller, S. W. (1997). Market talk: competition policy in America. Law & Social Inquiry, 22(2), 435-457. [15] Sexton, D. L. (2001). Wayne Huizenga: Entrepreneur and wealth creator. Academy of Management Perspectives, 15(1), 40-48. [16] White, B. (1986). Coase and the Courts: Economics for the Common Man. Iowa L. Rev., 72, 577. [17] Bufford, S. L. (2005). International Rule of Law and the Market Economy-An Outline. Sw. JL & Trade Am., 12, 303. [18] Harris, J. (2011). Jurisdiction and judgments in international trusts litigation -Surveying the landscape. Trusts & Trustees, Vol. 17, No. 4, May 2011, 236–260. [19] US Environmental Protection Agency. (1992). The United States Experience with Economic Incentives to Control Environmental Pollution. Washington, DC: US EPA-230-R-92-001. [20] Texas Parks & Wildlife (2018). Cedar Hill State Park. Retrieved 12/07/2018, from https://tpwd.texas.gov/state-parks/cedar-hill [21] Heiner, J. D., & Kockelman, K. M. (2005). Costs of right-of-way acquisition: Methods and models for estimation. Journal of Transportation Engineering, 131(3), 193-204. [22] Titus, J., Hudgens, D., Trescott, D., Craghan, M., Nuckols, W., Hershner, C., Kassakian, J., Linn, C., Merritt, P., & McCue, T. (2009). State and local governments plan for development of most land vulnerable to rising sea level along the US Atlantic coast. Environmental Research Letters, 4(4), 044008. [23] Pizzola, B. (2010). Free market environmentalism: The answer to government regulation. OrganizationTrends. Retrieved from http://capitalresearch.org/app/uploads/2013/07/OT0110.pdf [24] NOAA Fisheries. (2017). NOAA Catch Share Policy..Retrievedafromahttps://www.fisheries.noa.gov/national/laws-and-policies/catch-shares [25] Environmental Defense Fund. (2013). Catch Share Fisheries and Resources: Searchable Database. Retrieved.from.http://apps.edf.org/page.cfm?tagID=57622 [26] Schaefer, M. B. (1957). Some considerations of population dynamics and economics in relation to the management of the commercial marine fisheries. Journal of the Fisheries Board of Canada, 14(5), 669-681. [27] Schmalensee, R., & Stavins, R. (2015). Lessons learned from three decades of experience with cap-and-trade. [28] Schwartz, J., Pitcher, H., Levin, R., Ostro, B., & Nichols, A. L. (1985). Costs and benefits of reducing lead in gasoline: Final regulatory impact analysis. In Costs and benefits of reducing lead in gasoline: final regulatory impact analysis: EPA. [29] EPA. (2001). The United States Experience with Economic Incentives for Protecting the Environment. R. C. Anderson. Retrieved from https://yosemite.epa.gov/ee/epa/eerm.nsf/vwan/ee-0216b-07.pdf/$file/ee-0216b-07.pdf [30] Shelby, M., Shackleton, R., Shealy, M., & Cristofaro, A. (1997). The Climate Change Implications of Eliminating US Energy (and Related) Subsidies. Washington, DC: US Environmental Protection Agency. [31] TCEQ. (2016). Texas Emissions Reduction Plan: Biennial Report (2015-2016). Austin, Texas. Retrieved.from.https://www.tceq.texas.gov/assets/public/comm_exec/pubs/sfr/079-16.pdf